2022
DOI: 10.3390/cancers14204992
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammasomes Adaptor Protein PYCARD Is a Potential Pyroptosis Biomarker Related to Immune Response and Prognosis in Clear Cell Renal Cell Carcinoma

Abstract: PYCARD is a protein engaged in inflammation, pyroptosis, and apoptosis. However, the function of PYCARD in human cancers remains unclear. The objective of our study was to explore PYCARD expression and prognostic value in human cancers. Public databases were used to assess PYCARD expression and prognostic value. The TISIDB database was used to explore the associations between PYCARD expression and different immune subtypes. The correlations between PYCARD expression and ICP genes, MMR genes, MSI, and TMB were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been demonstrated that the expression of PYCARD is correlated with both the response to tumor immunotherapy and prognosis. Our data indicated that elevated levels of PYCARD in BC are linked to improved overall survival (OS), although the precise mechanism is not yet clear and requires further investigation in future studies ( 52 ).…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, it has been demonstrated that the expression of PYCARD is correlated with both the response to tumor immunotherapy and prognosis. Our data indicated that elevated levels of PYCARD in BC are linked to improved overall survival (OS), although the precise mechanism is not yet clear and requires further investigation in future studies ( 52 ).…”
Section: Discussionmentioning
confidence: 85%
“…These ndings illustrated that PYCARD could be a novel and potential biomarker for COPD. The in ammasome adaptor protein PYCARD (known as ASC) is a potential pyroptosis biomarker engaged in in ammation and related to immune response [40], which provides new insights into the pathogenesis of in ammatory diseases [41][42]. In addition, regarding function enrichment analysis, we demonstrated that PYCARD was mainly related to protein modi cation process, chemical stimulus, regulation of response to stimulus, and immune system process.…”
Section: Discussionmentioning
confidence: 89%
“…PYCARD, which is commonly known as apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), is the adaptor protein of inflammasomes and plays an important role in inflammation and pyroptosis. PYCARD contains a caspase activation and recruitment domain (CARD) and a pyrin domain (PYD) (35). Recent evidence revealed a crucial role of PYCARD in renal injury after UUO, and PYCARD deficiency reduces renal inflammation and fibrosis (36).…”
Section: Discussionmentioning
confidence: 99%